2004
DOI: 10.1021/jf035215h
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Induced Gelation of Pea Legumin:  Comparison with Soybean Glycinin

Abstract: Gel network formation of pea legumin (8.4% on a protein basis, pH 7.6) was monitored via dynamic rheological measurements. Gelation was performed in the absence and presence of the thiol-blocking reagent N-ethylmaleimide, at different rates of heating and cooling. Overall, it was shown that pea legumin gel formation was not effected by changes in the heating rate, and the two differently heated samples were unaffected by the addition of 20 mM NEM, which indicated that disulfide bonds were not essential within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(124 citation statements)
references
References 32 publications
9
108
1
1
Order By: Relevance
“…These observations are consistent with other studies which showed that pea protein isolate formed a paste instead of a rigid gel (Adebiyi and Aluko 2011). O'Kane et al (2004) stated that pea protein forms more unstructured gels than soy protein and thus their gelling properties are not as good as those of soy.…”
Section: Reconstitution Property and Stability Of Emulsions Reconstitsupporting
confidence: 92%
“…These observations are consistent with other studies which showed that pea protein isolate formed a paste instead of a rigid gel (Adebiyi and Aluko 2011). O'Kane et al (2004) stated that pea protein forms more unstructured gels than soy protein and thus their gelling properties are not as good as those of soy.…”
Section: Reconstitution Property and Stability Of Emulsions Reconstitsupporting
confidence: 92%
“…In the study of O'Kane, Happe, Vereijken, Gruppen, and van Boekel (2004), heating rate did not affect gel formation with pea legumin. However, it was observed that slower cooling of the legumin samples increased the gel strength.…”
Section: Introductionmentioning
confidence: 72%
“…They suggested that slow cooling could maintain the protein in its unfolded state for a longer time, slowing down the reactivity of the exposed residues, and enabling more optimal arrangement to occur, prior to interactions between proteins. Since hydrogen bonds are favored at low temperature and it has been confirmed that one of the main forces involved in promoting gel structure of pea legumin protein is the hydrogen bonds (O'Kane et al, 2004), it can be speculated that the hydrogen bond formation is enhanced at slower cooling rate resulting in stronger gels. O' Kane et al (2004) also indicated that under a slower cooling rate (1°C/min heating and 0.2°C/min cooling) hydrophobic interaction and disulfide bond are involved in formation of gel structure of pea legumin protein.…”
Section: Impact Of Cooling Rate On the Development Of Storage Modulusmentioning
confidence: 99%
“…49 Heat denaturation of legume protein would involve the exposure of hydrophobic residues, protein aggregation by intermolecular hydrophobic interaction and agglomeration of aggregates into a network structure. 25,50 The addition of legume flour also had an impact on the starch fraction. In the intermediate and central regions of pasta strand, legume starch granules could be differentiated from durum wheat starch by their different sizes and shapes.…”
Section: Discussionmentioning
confidence: 99%